Fintech dan Komunitas Berpenghasilan Rendah: Tinjauan Literatur Sistematis - Fahima Nasar; Abdul Hadi Sirat; Amran Husen; Hartaty Hadady (Society, 2025)
The current systematic literature review aimed to document the breadth of fintech research in low-income areas. Three papers that satisfied the inclusion requirements were found after a thorough search of the Scopus database published between January 2007 and October 2024 using PRISMA. The synthesis of these articles shows that fintech in low-income communities has been conducted in Africa, the United States, and the Netherlands. In addition, research on this theme also focuses on the water supply and sanitation industry, banking, and new holistic sanitation projects. Additionally, the transition and development theory is one of the theories employed to elucidate this relationship. This work presents theoretical and practical contributions and ideas for future research.